“Evaluación de los Sistemas Especiales de Importación- Exportación (Plan Vallejo), como instrumento de una política exportadora colombiana, desde el enfoque evaluación de productos”. - Soto Posada, Yorfany (Universidad Antonio Nariño, 2023)
The evaluation of public projects and programs is the result of activities for the evaluation of government actions the measure or assess performance in various areas, with a view to improving public policies. The objective of the research was to evaluate the Special Import - Export Systems (Plan Vallejo) as an instrument of the Colombian export policy, from the product evaluation approach. An Investigation of the type of exploratory-descriptive study with a qualitative approach method was carried out.